Groups Which Contain the Diffeomorphisms and Superdiffeomorphisms as Proper Subgroups - Dave Pandres (Journal of Mathematics)
We begin by recalling a group which is an enlargement of the diffeomorphisms on an ordinary manifold. We used this larger group to unify the gravitational and electroweak fields, which are mediated by bosons. Unfortunately, we could not include the neutrinos, because geometrical theories based on an ordinary manifold generally cannot include fermions. Therefore, in this paper, we introduce an analogous group that contains the superdiffeomorphisms on a DeWitt supermanifold as a proper subgroup.